MADURESE CONTROL - William D. Davies (K@ta: A Biannual Publication on the Study of Language and Literature, 2005)
This paper provides an overview of some characteristics of a Madurese grammatical construction in which the subject or object of the main verb supplies the reference for a nonovert participant in the complement, what is generally referred to under the rubric as 'control' in generative syntactic theory. The data indicate that control in Madurese shows some similarities to control in English and other languages, but that there are important differences as well.